Reformasi Birokrasi Publik Pasca Orde Baru: Perubahan tanpa 'Grand Design' - Miftah Thoha (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2000)
Normatively speaking bureaucratic reform is bound to be sensitive to the need for democratization, plurality and the advancement of information technology and global competition. Examination through several cases in this article leads us to conclude that the ongoing process of the attempted reform is missing its critical element: the grand design.